Thromboangiitis Obliterans: Current Perspectives and Future Directions - Ansari, Azam (1990)
Originally described by von Winiwarter in 1879 and by Buerger in 1908, thromboangiitis obliterans became a focus of delayed controversy in the 1960s when its existence as a separate entity came into question. More recently, new information regarding the disease's pathogenesis, as well as a redefinition of its clinical and roentgenographic features, has given further credence to the theory that thromboangiitis obliterans is a distinct clinicopathologic and roentgenographic entity. By critically analyzing both old and new insights, this article assesses the current status and future directions of the disease. (Texas Heart Institute Journal 1990;17:112-7)